Effect of Steel Fiber on Properties of High Performance No-Fine Concrete - M. F. Alwaan, Nada; ., .; ., . (International Journal of Engineering and Technology, 2018)
No-fine concrete (NFC) is cellular concrete and itâ€™s light weight concrete produced with the exclusion of sand from the concrete. This study includes the mechanical properties of lightweight reinforced by steel fiber, containing different proportions of steel fiber. This study was done using number of tests. These tests were density, compressive strength, flexural strength and absorption. These tests of the molds at different curing time. The results of tests that implication of fiber to No. fine concrete did not affect significantly on the compressive strength, While the flexural strength were gets better. Results explained that, the flexural strength of (1%) fiber No- fine concrete molds are four times that of the reference molds in age 28 days. The growing in flexural strength for fiber reinforced mixes with fiber by vol. (0.5%, 0.75%, 1%) were (78%, 132%, 286%) respectively at age of 28 days.Â